The wise man always brings salvation to people - beyond the limits of imagination: reflecting on the humanistic message of Princess Mononoke as the center of Hayao Miyazaki’s filmwork - Braszka, Justyna (Hybris, 2022)
The article focuses on several themes that make up the body of Hayao Miyazakis Princess Mononoke — an anime film dominated by environmental themes. The article presents the message of the film, which at the same time corresponds to other works by the Japanese director. Therefore, the article presents a film studies perspective that includes the analysis of film. Apart from that, the article presents other perspectives: anthropological - discussion of non-human beings and showing themes from Japanese folklore, and historical and social ones, which include open criticism of contemporary society and the influence of postcolonial thought.